A modified damped Gauss–Newton method for non-monotone weighted linear complementarity problems. (4th May 2022) - Tang, Jingyong; Zhou, Jinchuan
Abstract : We consider the weighted linear complementarity problem (denoted by wLCP). Many numerical algorithms have been proposed for solving the monotone wLCP. In this paper, we propose a damped Gauss–Newton method to solve the non-monotone wLCP which is designed based on a derivative-free non-monotone line search. We show that the proposed method is well defined and it is globally convergent without any problem assumptions. Moreover, we analyze the local quadratic convergence of the proposed method under the non-singularity condition and the local error bound condition, respectively. Our method not only has encouraging local convergence properties but also can be used to solve non-monotone wLCPs. Preliminary numerical results are reported.